Chemical and Microbiological Characteristics of Kombucha Beverage Produced from Robusta and Arabica Coffee with Varied Roasting Profiles - Savitri, Dyah Ayu; Setiyono, Setiyono; Meliala, Susan Barbara Patricia Sembiring; Arum, Ayu Puspita; Novijanto, Noer; Herliani, Canserlita Puteri (Journal of Applied Agricultural Science and Technology, 2024)
Kombucha is a fermented beverage product often produced by adding kombucha culture into sweetened tea, juices, coffee, and herb extracts. Coffee is a refreshing ingredient commonly served as a beverage prepared from roasted coffee beans. Therefore, this study aimed to investigate the chemical and microbiological characteristics of kombucha beverage produced from robusta and arabica coffee through natural methods with light, medium, and dark roasting profiles. Ground-roasted robusta and arabica coffee were dissolved into a sucrose solution, then the kombucha culture was added to these treatments and fermented for 14 days at ambient temperature. Subsequently, each kombucha beverage was analyzed for Total Soluble Solid (TSS), pH, Total Titrated Acid (TTA), Soluble Vitamin C, Caffeine Content, and Total Lactic Acid Bacteria (LAB). The results showed that TSS decreased on the 14th day due to sucrose degradation by microbes. TTA increased at the end of the processing, followed by a lower pH (2.87–3.49), signifying a safe value for human consumption. The soluble Vitamin C increased on the seventh day and decreased on the 14th day, which was related to the oxidation process during fermentation. The monoanion of ascorbic acid became oxidized by oxygen molecules and formed other unstable compounds. The total LAB and caffeine content elevated along with fermentation time due to the caffeine solubility which increased in low pH solution.